Pernikahan dalam Adat Gayo: Tradisi dan Kebudayaan - Mudrika, Annisa Dea; Astari, Novia; Siregar, Yusra Dewi (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
This study aims to examine the marriage traditions and culture within the Gayo community, with a focus on understanding the meanings and values embedded in them. Through a qualitative ethnographic approach, data were collected through direct observation, in-depth interviews, and literature analysis. The research reveals that the Gayo traditional marriage procession consists of a series of stages reflecting the values of togetherness, social harmony, and religiosity. Traditions such as merisik (ngekik), proposing (berihi), setting the wedding date (bohke), and the wedding ceremony (ngunduh) are key elements that reinforce Gayo's cultural identity. This study also highlights the role of traditional marriage in preserving cultural continuity and tradition amidst social change. The findings of this research are expected to contribute to the preservation of Gayo's cultural heritage and provide deeper insights into the importance of marriage traditions as a reflection of the Gayo community's identity.